1982
DOI: 10.1128/aem.43.3.590-596.1982
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of coliphages T1 and T7 to clay minerals

Abstract: Coliphages T1 and T7 of Escherichia coli were absorbed by kaolinite (K) and montmorillonite (M). Maximum adsorption of T7 (96%) to M was greater than that of T1 (84%), but the adsorption of both coliphages to K was the same (99%). Positively charged sites (i.e., anion exchange sites) on the clays appeared to be primarily responsible for the adsorption of T1 to K but only partially responsible for the adsorption of T1 to M; equilibrium adsorption isotherms of T1 to K and M did not show a correlation between ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 27 publications
2
35
1
2
Order By: Relevance
“…The association of viruses with clay minerals has been attributed to the large surface area and high cation exchange capacity (CEC) of clays. The mechanisms and sites of sorption differ for different viruses and are influenced by characteristics of the clays such as anion exchange capacity (AEC), CEC, and AEC to CEC ratios (Schiffenbauer and Stotzky, 1982). Both positively and negatively charged sites on clay minerals are involved in virus sorption.…”
Section: Clay Mineralssupporting
confidence: 72%
See 1 more Smart Citation
“…The association of viruses with clay minerals has been attributed to the large surface area and high cation exchange capacity (CEC) of clays. The mechanisms and sites of sorption differ for different viruses and are influenced by characteristics of the clays such as anion exchange capacity (AEC), CEC, and AEC to CEC ratios (Schiffenbauer and Stotzky, 1982). Both positively and negatively charged sites on clay minerals are involved in virus sorption.…”
Section: Clay Mineralssupporting
confidence: 72%
“…Lipson andStotzky (1983, 1985) found that reovirus was sorbed more onto montmorillonite than onto kaolinite. Schiffenbauer and Stotzky (1982) showed that maximum sorption of coliphages ite was one of the least effective minerals in virus sorption. Insufficient information is available from the φX174 in saturated California soil column.…”
Section: Clay Mineralsmentioning
confidence: 99%
“…Although the literature has focused on the effect of environmental conditions (clay type, clay charge distribution [Lipson and Stotzky 1985;Christian et al 2006;Templeton et al 2008], pH [Zhuang and Jin 2008;Walshe et al 2010], ionic strength [Tong et al 2012], buffer composition [Zhuang and Jin 2008;Gutierrez et al 2010], and cation exchange capacity [Lipson and Stotzky 1983;Vettori et al 1999]), the surface morphology of viruses has been largely ignored. The attachment of phages T1, T7, T2, PBS1, or φX174 to cation exchanged clay is related to positively charged sites on clay edges (Schiffenbauer and Stotzky 1982;Chattopadhyay and Puls 1999;Vettori et al 2000). However, Lipson and Stotzky (1983) found that reovirus adsorption occurs at negatively charged sites on cation exchanged kaolinite and MMT, consistent with Derjaguin, Landau, Verwey, Overbeek (DLVO) (Derjaguin and Landau 1941;Verwey and Overbeek 1948) theory of colloidal aggregation.…”
Section: Introductionmentioning
confidence: 74%
“…The experimental and control were centrifuged at 8000 Â g for 10 min, followed by decanting of the supernatant, and then fixation of the bacteria for 5 min in 1% glutaraldehyde/4% paraformaldehyde. Five microliter of the fixed bacterial preparation were placed on formvar-coated, 300-mesh grids for 5 min followed by staining with phosphotungstic acid for 15 s. Excess fluid was removed with absorbent paper (Schiffenbauer and Stotzky, 1982). Specimens were examined using an Amray 1850-FE scanning electron microscope.…”
Section: Electron Microscopymentioning
confidence: 99%